Prophylactic Use of Clopidogrel in Paediatric Cardiac Patients - Hanke, C. A.; Stiller, B.; Nakamura, L.; Grohmann, J.; Zieger, B. (Klinische Pädiatrie, 2012)
Thromboembolic complications in infants with congenital heart defects are common despite inhibition of platelet function with acetylsalicylic acid (ASS). Yet there is still insufficient pharmacologic data on the use of clopidogrel in infants. The adult dose of 75 mg/d is significantly higher than the dose lately recommended in infants (0.2 mg/kg/d). Moreover, we know of nonresponders to both acetylsalicylic acid and clopidogrel. Normal coagulation tests fail to identify those patients.Prospective monocentric study on 14 children (median age 5, range 0.7–84 months, 9 male, 5 female). Shunt thrombosis had occurred in 4 infants on ASS therapy. Seven days after starting clopidogrel (0.2 mg/kg/d), platelet function was tested by stimulation with ADP (4 and 10 µmol/l). We considered the range for the clopidogrel effect to be optimal if the maximum aggregation on ADP 4 µmol/l was between 30–50%.Clopidogrel 0.18–0.24 mg/kg/d in addition to ASS 2–4 mg/kg/d resulted in effective inhibition of platelet function in 93% (ADP 4 µmol/l: median 38%, range 30–63). All patients were responders. We observed neither any thromboembolic events nor severe bleeding episodes during the median 11-month follow-up period (range 1–30 mo).Testing platelet function makes clopidogrel dosing safer, and simplifies therapy adjustments in long-term treatment. A clopidogrel dose of 0.2 mg/kg/d was safe and effective in combination with ASS in this small patient cohort.
Keywords: treatment; platelet inhibition; children; platelet function